Effect of the Added Acyl Homoserine Lactones on Separated Free-Living Marine Bacteria as a Model of Quorum Sensing - Gary E. Schultz; Peter H. Santschi (Journal of Marine Science and Engineering, 2023)
Quorum sensing is a communication system by which bacteria use signal molecules to induce a physiological response. In natural marine environments, quorum sensing is suspected to occur in regions with high cell densities. Free-living bacteria, however, are largely believed to exist at concentrations too low to make use of a density-dependent quorum-sensing system. Due to so-called ‘free-living’ bacteria inhabiting marine gels composed of exopolymeric substances occurring in an operationally defined colloidal fraction, it is possible that quorum-sensing molecules would also occur in this fraction. In this study, possible signaling molecules were collected from marine water, separated, and concentrated as some organic matter. Their identification with an Agrobacterium tumefaciens assay indicated the presence of AHLs. In fall 2002 and spring 2003, free-living (single cells) fraction of marine bacterioplankton was sampled and separated. Various AHLs were added to these disperse populations (109 cells/L). The studied bacterial communities responded with change in the thymidine incorporation. The results are discussed as existence of active reaction of marine free-living bacteria to signaling molecules even in sparse inhabiting marine gels. That there is a bacterial response to signaling molecules in so sparse populations is of great significance for marine and environmental sciences.